An integrative review exploring decision‐making factors influencing mental health nurses in the use of restraint. Issue 2 (26th January 2016) - Riahi, S.; Thomson, G.; Duxbury, J.
Accessible Summary: What is known on the subject?: There is emerging evidence highlighting the counter therapeutic impact of the use of restraint and promoting the minimization of this practice in mental health care. Mental health nurses are often the professional group using restraint and understanding factors influencing their decision‐making becomes critical. To date, there are no other published papers that have undertaken a similar broad search to review this topic. What this paper adds to existing knowledge?: Eight emerging themes are identified as factors influencing mental health nurses decisions‐making in the use of restraint. The themes are: 'safety for all', 'restraint as a necessary intervention', 'restraint as a last resort', 'role conflict', 'maintaining control', 'staff composition', 'knowledge and perception of patient behaviours', and 'psychological impact'. 'Last resort' appears to be the mantra of acceptable restraint use, although, to date, there are no studies that specifically consider what this concept actually is. What are the implications for practice?: These findings should be considered in the evaluation of the use of restraint in mental health settings and appropriate strategies placed to support shifting towards restraint minimization. As the concept of 'last resort' is mentioned in many policies and guidelines internationally with no published understanding of what this means, research should prioritize this as a critical next step in restraint minimization efforts. Abstract: Introduction: While mechanical and manual restraint as an institutional method of control within mental health settings may be perceived to seem necessary at times, there is emergent literature highlighting the potential counter‐therapeutic impact of this practice for patients as well as staff. Nurses are the professional group who are most likely to use mechanical and manual restraint methods within mental health settings. In‐depth insights to understand what factors influence nurses' decision‐making related to restraint use are therefore warranted. Aim: To explore what influences mental health nurses' decision‐making in the use of restraint. Method: An integrative review using Cooper's framework was undertaken. Results: Eight emerging themes were identified: 'safety for all', 'restraint as a necessary intervention', 'restraint as a last resort', 'role conflict', 'maintaining control', 'staff composition', 'knowledge and perception of patient behaviours', and 'psychological impact'. These themes highlight how mental health nurses' decision‐making is influenced by ethical and safety responsibilities, as well as, interpersonal and staff‐related factors. Conclusion: Research to further understand the experience and actualization of 'last resort' in the use of restraint and to provide strategies to prevent restraint use in mental health settings are needed.